Biochemical characterization of serine acetyltransferase and cysteine desulfhydrase from Leishmania major - Marciano, Daniela Analia (2010)
Cysteine metabolism exhibits atypical features in Leishmania parasites. The nucleotide sequence annotated as LmjF32.2640 encodes a cysteine desulfhydrase, which specifically catalyzes the breakdown of cysteine into pyruvate, NH(3) and H(2)S. Like in other pathogens, this capacity might be associated with regulatory mechanisms to control the intracellular level of cysteine, a highly toxic albeit essential amino acid, in addition to generate pyruvate for energy production. Besides, our results provide the first insight into the biochemical properties of Leishmania major serine acetyltransferase (SAT), which is likely involved in the two routes for de novo synthesis of cysteine in this pathogen. When compared with other members of SAT family, the N-terminal region of L. major homologue is uniquely extended, and seems to be essential for proper protein folding. Furthermore, unlike plant and bacterial enzymes, the carboxy-terminal-C(10) sequence stretch of L. major SAT appears not to be implicated in forming a tight bi-enzyme complex with cysteine synthase.